Pembelajaran Online Selama Pandemi Covid-19 oleh Mahasiswa Pendidikan Kimia: Bentuk, Implementasi dan Harapan - Dedi Futra*; Indra Primahardani; Riki Apriyandi Putra; Sri Wilda Albeta (Universitas Syiah Kuala, 2021)
Since the corona virus disease (Covid-19) was found in patients in Wuhan, China and this virus has shown rapid transmission and has become a worldwide epidemic. As a result, online learning is applied to all universities in Indonesia by using various applications. This work is aimed for analyzing the implementation of online learning during the Covid -19 pandemic and is directed for investigating the form, implementation and expectations of students in online learning. This research was involved 231 samples consisting of all chemistry education student at Universities in Riau. The data directly collected through e-questionnaire using google form. The data obtained from the questionnaire were analyzed quantitatively and the interview data in the form of short questions were analyzed qualitatively. All the obtained data were carfully described in descriptive form. Basid oh the analysis, it was found that the type of online learning was dominated by using google classroom and zoom meeting, while the type of online learning was popularly used by student in the form of google classroom. Methods and obstacles in online learning were found using discussion approaches and internet networks, respectively. Meanwhile, the analysis of implementation and expectations in online learning were found the student responses with both in the agreed category with a value of more than 50%. Based on the data findings, the students of chemistry education have applied online learning, even though there are still many obstacles faced in online learning